Standing second sound wave in many-layer systems - Nemchenko, K.; Rogova, S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
The variation of thermodynamic parameters of superfluid helium in standing second sound wave is studied. Such double-layer systems as heater–helium and helium–detector are considered. Heat transfer in the heater and the detector was described with usual thermal conductivity equation. Temperature and heat transfer in superfluid 4He was described with the system of equations for superfluid with taking into accounts both dissipative thermal conductivity mode and second sound mode. Resonance frequency and amplitude dependence on dissipation at the heater and the detector was studied. The unusual resonance was found in the double-layer system helium– detector.